Scalable graphene electro–optical modulators for all-fibre pulsed lasers. Issue 21 (25th May 2021) - Lau, Kuen Yao; Pyymaki Perros, Alexander; Li, Diao; Kim, Maria; Sun, Zhipei
Abstract : Here, we report scalable graphene electro–optical modulators for all-fibre pulsed laser applications, promising for various applications such as medical treatment, material processing, and spectroscopy. Abstract : Recently, graphene electro–optical modulators have emerged as a viable alternative to the conventional modulators due to their broadband operation, ultrafast responsivity, small footprint, and low energy consumption. Here, we report scalable graphene electro–optical modulators for all-fibre pulsed laser applications. An actively Q-switched all-fibre laser is demonstrated with a scalable graphene electro–optical modulator for the first time, which is different from the previously reported work that typically implemented graphene electro–optical modulators in a free-space optical system. Our electrically modulated actively Q-switched fibre laser outputs at the centre wavelength of ∼1961.9 nm, the tunable repetition rate of 56.5 to 62.5 kHz, the maximum pulse energy of ∼80 nJ, and the signal-to-noise ratio of ∼46.6 dB. This work demonstrates that the scalable all-fibre integrated graphene electro–optical modulator approach is promising for producing pulsed fibre lasers at 2 μm with high performance and easy integration which are useful in various applications such as medical treatment, material processing, and spectroscopy.